A polyphenylene sulfide polyamide composite material and its preparation and application

By introducing components such as polyamide and glass fiber into polyphenylene sulfide, polyphenylene sulfide polyamide composite materials with improved tensile strength, notch impact strength, CTI and bonding strength were prepared, and polyphenylene sulfide was solved. In the application, poor toughness and low impact strength have expanded its application areas.

CN116355410BActive Publication Date: 2025-02-14辰东意普万新材料(广东)有限公司 +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310574132.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-22
Publication Date
2025-02-14
Estimated Expiration
2043-05-22

AI Technical Summary

Technical Problem

Polyphenylene sulfide (PPS) has problems such as poor toughness, low impact strength, low CTI and weak mutual adhesion properties in applications, which limits its application in high temperature and high humidity environments.

Method used

Using polyphenylene sulfide polyamide composite material, the polyphenylene sulfide resin, copolypolyamide, glass fiber and other additives are premixed in a specific proportion and melted and extruded at high temperature through a twin screw extruder to prepare the Composite materials that improve tensile strength, notch impact strength, CTI and bonding strength.

Benefits of technology

It significantly improves the tensile strength, notch impact strength, CTI and bonding strength of polyphenylene sulfide polyamide composite materials, and expands its use in electronics, electrical appliances, automobiles, nano injection molding, precision instruments, 5G communications, chemicals, aerospace, etc. Application scope of the field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004239417900000021
    Figure BDA0004239417900000021
  • Figure BDA0004239417900000051
    Figure BDA0004239417900000051
  • Figure BDA0004239417900000061
    Figure BDA0004239417900000061
Patent Text Reader

Abstract

The present invention belongs to the field of composite materials, and discloses a polyphenylene sulfide polyamide composite material and its preparation and application. The polyphenylene sulfide polyamide composite material comprises the following components in parts by mass: 35-96 parts of polyphenylene sulfide resin; 3-35 parts of copolyamide; 0-50 parts of glass fiber; 0-2.0 parts of coupling agent, 0-1.0 parts of nucleating agent; 0-1.0 parts of lubricant; 0-1.0 parts of antioxidant, and the copolyamide is a copolyamide with a melting point of 50°C-200°C. The polyphenylene sulfide polyamide composite material prepared by the present invention has significantly improved tensile strength, notched impact strength, CTI, bonding strength, etc. of the obtained polyphenylene sulfide polyamide composite material relative to conventionally used polyamide resins such as PPA, PA66, PA6, etc. It has good applications in the fields of electronics, electrical appliances, automobiles, nano injection molding, precision instruments, 5G communications, chemical industry, aerospace, etc.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of composite materials, and particularly relates to a polyphenylene sulfide polyamide composite material and a preparation method and application thereof. Background Art

[0002] PPS is one of the most heat-resistant engineering plastics. After being modified with glass fiber, its heat deformation temperature is greater than 260 degrees, and its chemical resistance is second only to polytetrafluoroethylene. In addition, it also has the advantages of small molding shrinkage, low water absorption, good fire resistance, good fatigue resistance, and high breakdown voltage. In particular, it still has excellent electrical insulation in high temperature and high humidity environments. However, PPS has poor toughness, low impact strength, low CTI (relative tracking index), and weak mutual adhesion, which also limits its application areas. Therefore, it is necessary to modify it to solve the above shortcomings, so as to obtain excellent comprehensive performance. Summary of the invention

[0003] In order to overcome the shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a polyphenylene sulfide polyamide composite material.

[0004] Another object of the present invention is to provide a method for preparing the polyphenylene sulfide-polyamide composite material.

[0005] Another object of the present invention is to provide applications of the above-mentioned polyphenylene sulfide polyamide composite material in the fields of electronics, electrical appliances, automobiles, nano injection molding, precision instruments, 5G communications, chemical industry, aerospace, etc.

[0006] The purpose of the present invention is achieved through the following solutions:

[0007] A polyphenylene sulfide polyamide composite material, comprising the following components in parts by weight:

[0008] 35-96 parts of polyphenylene sulfide resin; 3-35 parts of copolymerized polyamide; 0-50 parts of glass fiber; 0-2.0 parts of coupling agent, 0-1.0 parts of nucleating agent; 0-1.0 parts of lubricant; and 0-1.0 parts of antioxidant.

[0009] Preferably, the polyphenylene sulfide polyamide composite material comprises the following components in parts by weight:

[0010] 40-70 parts of polyphenylene sulfide resin; 3-20 parts of copolymerized polyamide; 30-40 parts of glass fiber; 0.1-0.5 parts of coupling agent, 0.1-0.5 parts of nucleating agent; 0.1-0.5 parts of lubricant; 0.1-0.5 parts of antioxidant.

[0011] The polyphenylene sulfide resin is selected from resins having a melt index range of 250-700 g / 10 min measured under the conditions of 316° C. / 5 kg.

[0012] The copolyamide is preferably a copolyamide with a melting point of 50° C.-200° C., and more preferably at least one of the copolyamides with a melting point of 95° C.-170° C. A further preferred copolyamide is synthesized from caprolactam, hexamethylenediamine, decanediamine, sebacic acid, and dodecane dicarboxylic acid as raw materials at a certain mass molar ratio, wherein the molar ratio of caprolactam, hexamethylenediamine, decanediamine, sebacic acid, and dodecane dicarboxylic acid is 8:(2-10):(2:10):(3-6):(6-9).

[0013] The melting point and density of the copolymerized polyamide resin are shown in Table 1 below:

[0014] Table 1 Melting point and density of different grades of polyamide resin

[0015]

[0016] Preferably, the molar ratio of caprolactam, hexamethylenediamine, decanediamine, sebacic acid and dodecanedioic acid in the copolymer polyamide 1# is 8:6:6:6:6; the molar ratio of caprolactam, hexamethylenediamine, decanediamine, sebacic acid and dodecanedioic acid in the copolymer polyamide 2# is 8:6:6:3:9; the molar ratio of caprolactam, hexamethylenediamine, decanediamine, sebacic acid and dodecanedioic acid in the copolymer polyamide 3# is 8:2:10:3:9; the molar ratio of caprolactam, hexamethylenediamine, decanediamine, sebacic acid and dodecanedioic acid in the copolymer polyamide 4# is 8:10:2:3:9.

[0017] The glass fiber is preferably a round glass fiber with a diameter of 9-13 μm and a short cut length of 3.0-5.0 mm or a flat glass fiber with a flatness of 2-5.

[0018] The coupling agent is at least one of an amino silane coupling agent, an acyloxy silane coupling agent, an alkoxy silane coupling agent and an epoxy silane coupling agent, preferably at least one of N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, vinyltri(methoxyethoxy)silane, vinyltrimethoxysilane, 3(2,3-epoxypropyloxy)propyltrimethoxysilane, more preferably at least one of commercially available N-β-(aminoethyl)γ-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, and 3(2,3-epoxypropyloxy)propyltrimethoxysilane models;

[0019] The nucleating agent is at least one of talc, calcium carbonate, glass beads, silicon dioxide, calcium oxide, magnesium oxide, carbon black, mica, and molybdenum disulfide, and more preferably talc.

[0020] The lubricant is at least one of stearic acid metal salts, pentaerythritol stearate, ethylene bisstearamide, erucic acid amide, oleic acid amide, silicones, polyolefin wax, etc., preferably pentaerythritol stearate.

[0021] The antioxidant is at least one of hindered phenol antioxidants, hindered amine antioxidants, o-hydroxyphenyltriazine antioxidants, phosphite antioxidants and thioester antioxidants.

[0022] A method for preparing the above-mentioned polyphenylene sulfide polyamide composite material comprises the following steps:

[0023] First, the remaining raw materials except the glass fiber are premixed to obtain a premix, and then the premix is ​​discharged from the main feeding port of the twin-screw extruder, and the glass fiber is discharged from the side feeding port of the twin-screw extruder. The premix + glass fiber are melt-extruded at 250-330° C. through the twin-screw extruder, and the polyphenylene sulfide polyamide composite material is obtained by cooling and pelletizing.

[0024] Alternatively, the remaining raw materials except the glass fiber and the coupling agent are premixed to obtain a premix, and then the premix is ​​discharged from the main feeding port of the twin-screw extruder, the glass fiber is discharged from the side feeding port of the twin-screw extruder, and the coupling agent is metered and added at a set ratio at the liquid filling port of the extruder. The premix + glass fiber + coupling agent are melt-extruded at 250-330° C. through the twin-screw extruder, cooled, and pelletized to obtain the polyphenylene sulfide polyamide composite material.

[0025] The nucleating agent, lubricant and antioxidant are preferably first mixed uniformly to form a compound package, and then premixed with other raw materials to obtain a premix.

[0026] The above-mentioned polyphenylene sulfide polyamide composite material is used in the fields of electronics, electrical appliances, automobiles, nano injection molding, precision instruments, 5G communications, chemical industry, aerospace, etc.

[0027] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0028] The invention provides a scheme for preparing a polyphenylene sulfide polyamide composite material. The tensile strength, notched impact strength, CTI, bonding strength and the like of the obtained polyphenylene sulfide polyamide composite material are significantly improved. DETAILED DESCRIPTION

[0029] The present invention is further described in detail below in conjunction with comparative examples and examples, but the embodiments of the present invention are not limited thereto. Where specific conditions are not specified in the comparative examples and examples, the conditions are carried out under conventional conditions or conditions recommended by the manufacturer. Where the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0030] The preparation methods of the copolymer polyamides in the comparative examples and embodiments are described in the preparation method description section. The remaining raw materials can be obtained commercially, specifically as follows: polyphenylene sulfide is Xinhecheng 1150C, PA66 is BASF Ultramid A3L, PA6 is Yuehua YH-800, PPA is Xinhecheng NH600, glass fiber is Chongqing International ECS10-03-584, coupling agent is Shin-Etsu KBE-903, antioxidant is Tianjin Lianlong 1010, nucleating agent is Xufeng BHS-503, and lubricant is Corning LOXIOL P861 / 3.5.

[0031] Copolyamide 1#, copolyamide 2#, copolyamide 3#, and copolyamide 4# in Examples 1-11 and Comparative Example 6 are prepared from caprolactam, hexamethylenediamine, sebacic acid, decanediamine, and dodecanedioic acid by a monomer melt polymerization method. The specific raw material amounts and the synthesis process are shown in Table 2 below:

[0032] Table 2 Raw material types and molar amounts of copolymer polyamide 1#, copolymer polyamide 2#, copolymer polyamide 3#, and copolymer polyamide 4#

[0033] The preparation method of the composite material in Comparative Examples 1-5 and Examples 1-8 comprises the following steps:

[0034] (1) Weigh each raw material according to the ratio of each raw material component, premix the resin + additive compound package in a mixer for 3 minutes, and then discharge the resulting premix through the main feeding port of a twin-screw extruder;

[0035] (2) Glass fiber is fed from the side feed port of the twin-screw extruder;

[0036] (3) The coupling agent is added at the liquid filling port of the extruder;

[0037] (4) The premix + glass fiber + coupling agent are melt-extruded at 250-330° C. through a twin-screw extruder, cooled, and pelletized to prepare a polyphenylene sulfide polyamide composite material.

[0038] Then, injection molding specimens of thermoplastic materials were made according to ISO294-1-2018 standard, where the processing mold temperature was 135°C and the injection molding processing temperature was 295-330°C. The obtained specimens were subjected to corresponding tensile strength, notch impact, flame retardant properties, CTI tests, and bonding strength tests. The tensile strength test was conducted using ISO 527 standard, the impact strength test was conducted using ISO 180 standard, the flame retardant test was conducted using IEC60695-11-10 standard, and the CTI index was tested using IEC 60112 standard method. The bonding performance test simulated the ISO 527-2 standard test, using an injection-molded 1A dumbbell-shaped spline, which was cut in the middle and coated with glue, and the bonding area between the two splines was 40mm. 2 The thickness of the glue layer is 0.2mm, and the glue used is Wilbond 5354 (glue heating temperature 125℃). After curing for 24 hours in an environment with a temperature of 23℃ and a relative humidity of 55%, the tensile strength test is carried out.

[0039] Comparative Examples 1-5 and Examples 1-8

[0040] The formulas of the composite materials in Comparative Examples 1-5 and Examples 1-8 and the results of the material testing items are specifically shown in Table 3 below:

[0041] Table 3 Formulas of composite materials in comparative examples 1-5 and examples 1-8 and results of material testing items

[0042]

[0043]

[0044] The amounts of resin, glass fiber, coupling agent and additives mentioned above are all percentages by weight, in %.

[0045] It can be seen from Table 3 that when copolyamide and polyphenylene sulfide are used for compounding, the tensile strength, notched impact strength, CTI, bonding strength, etc. of the obtained composite material are significantly improved compared with the commonly used PPA, PA66, PA6, etc., and more excellent performance can be obtained. In Example 8, when the ratio of copolyamide to polyphenylene sulfide resin in the composite is 20:39, the flame retardant performance of the material is V1 level. In Examples 1-7, when the ratio of copolyamide to polyphenylene sulfide is lower than that in Example 8, the flame retardant performance of the composite is V0.

[0046] Comparative Examples 6-8 and Examples 9-11

[0047] The formulas of the composite materials in Comparative Examples 6-8 and Examples 9-11 and the results of the material testing items are specifically shown in Table 4 below:

[0048] Table 4 Formulas of composite materials in comparative examples 6-8 and examples 9-11 and results of material testing items

[0049]

[0050]

[0051] The preparation methods of the composite materials in Comparative Examples 6-8 and Examples 9-11 are substantially the same as those in Examples 1-8, except that the coupling agent is added in different ways, as follows:

[0052] (1) Weigh each raw material according to the ratio of each raw material component in Table 4, then premix the resin + coupling agent + auxiliary agent in a mixer for 3 minutes, and then discharge the resulting premix through the main feeding port of a twin-screw extruder;

[0053] (2) Glass fiber is fed from the side feed port of the twin-screw extruder;

[0054] (3) the premix + side material are melt-extruded at 250-330° C. through a twin-screw extruder, cooled, and pelletized to prepare a polyphenylene sulfide polyamide composite material;

[0055] Then, the sample preparation and testing were carried out in the same manner as in Example 1-8. The test results are shown in Table 4.

[0056] As can be seen from Table 4, the performance of the scheme of metering the coupling agent at the liquid filling port of the extruder is significantly better than the traditional process of adding the coupling agent to the main feed through the premix. Because the traditional process requires a mechanical mixer to operate for 3-10 minutes to mix evenly when the main feed is mixed, and the silane coupling agent will hang and volatilize during the mixing process, and the coupling agent is very easy to react with air moisture or material surface moisture, and the substrate will also produce lumps after the reaction, resulting in processing difficulties and uneven processing, which will reduce its efficacy compared to the actual addition amount. By directly injecting it into the liquid filling port of the extruder, the timeliness and accuracy of the mixing performance of the traditional main feed are higher.

[0057] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A polyphenylene sulfide polyamide composite material, characterized in that The composition includes the following components in parts by weight: 35-96 parts of polyphenylene sulfide resin; 3-35 parts of copolymerized polyamide; 0-50 parts of glass fiber; 0-2.0 parts of coupling agent, 0-1.0 parts of nucleating agent; Lubricant 0-1.0 part; Antioxidant 0-1.0 part; The copolyamide is a copolyamide with a melting point of 50°C-200°C; The copolymer polyamide is synthesized from caprolactam, hexamethylenediamine, decanediamine, sebacic acid and dodecanedioic acid as raw materials, wherein the molar ratio of caprolactam, hexamethylenediamine, decanediamine, sebacic acid and dodecanedioic acid is 8:(2-10):(2:10):(3-6):(6-9).

2. The polyphenylene sulfide polyamide composite material according to claim 1, characterized in that The composition includes the following components in parts by weight: The polyphenylene sulfide resin is 40-70 parts; the copolymer polyamide is 3-20 parts; the glass fiber is 30-40 parts; the coupling agent is 0.1-0.5 parts, the nucleating agent is 0.1-0.5 parts; the lubricant is 0.1-0.5 parts; and the antioxidant is 0.1-0.5 parts.

3. The polyphenylene sulfide polyamide composite material according to claim 1, characterized in that: The polyphenylene sulfide resin is selected from resins having a melt index range of 250-700 g / 10 min measured under the conditions of 316° C. / 5 kg.

4. The polyphenylene sulfide polyamide composite material according to claim 1, characterized in that: The copolyamide is a copolyamide with a melting point of 95-170°C.

5. The polyphenylene sulfide polyamide composite material according to claim 4, characterized in that: The copolyamide is a copolyamide with a melting point of 115-160°C.

6. The polyphenylene sulfide polyamide composite material according to claim 1, characterized in that: The glass fiber is a round glass fiber with a diameter of 9-13 μm and a short cut length of 3.0-5.0 mm or a flat glass fiber with a flatness of 2-5.

7. The polyphenylene sulfide polyamide composite material according to claim 1, characterized in that: The coupling agent is at least one of an amino silane coupling agent, an acyloxy silane coupling agent, an alkoxy silane coupling agent and an epoxy silane coupling agent.

8. The polyphenylene sulfide polyamide composite material according to claim 7, characterized in that: The coupling agent is at least one of N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, vinyltri(methoxyethoxy)silane, vinyltrimethoxysilane and 3-(2,3-epoxypropyloxy)propyltrimethoxysilane.

9. The polyphenylene sulfide polyamide composite material according to claim 1, characterized in that: The nucleating agent is at least one of talc, calcium carbonate, glass beads, silicon dioxide, calcium oxide, magnesium oxide, carbon black, mica, and molybdenum disulfide; The lubricant is at least one of stearic acid metal salts, pentaerythritol stearate, ethylene bisstearamide, erucic acid amide, oleic acid amide, silicones, and polyolefin wax; The antioxidant is at least one of hindered phenol antioxidants, hindered amine antioxidants, o-hydroxyphenyltriazine antioxidants, phosphite antioxidants and thioester antioxidants.

10. A method for preparing the polyphenylene sulfide polyamide composite material according to any one of claims 1 to 9, characterized in that The following steps are involved: Firstly, the remaining raw materials except glass fiber are premixed to obtain a premix, and then the premix is ​​discharged from the main material port of the twin-screw extruder, and the glass fiber is discharged from the side material port of the twin-screw extruder. The premix and the glass fiber are melt-extruded at 250-330° C. through the twin-screw extruder, and then cooled and pelletized to obtain a polyphenylene sulfide polyamide composite material; Alternatively, the remaining raw materials except the glass fiber and the coupling agent are premixed to obtain a premix, and then the premix is ​​discharged from the main feeding port of the twin-screw extruder, the glass fiber is discharged from the side feeding port of the twin-screw extruder, and the coupling agent is added at the liquid filling port of the extruder. The premix, glass fiber and coupling agent are melt-extruded at 250-330° C. through the twin-screw extruder, cooled and pelletized to obtain the polyphenylene sulfide polyamide composite material.

11. Application of the polyphenylene sulfide polyamide composite material according to any one of claims 1 to 9 in the fields of electronics, electrical appliances, automobiles, laser welding, precision instruments, 5G applications, chemical industry, and aerospace.

Citation Information

Patent Citations

  • Polyphenylene sulfide resin composition

    CN101061182A